EVALUASI PEMBENTUKAN KANTOR PERIZINAN TERPADU DALAM PEMBERIAN IZIN USAHA INDUSTRI PRIMER HASIL HUTAN - Epi Syahadat; Subarudi Subarudi; Andri Setiadi Kurniawan (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2018)
Establishing Integrated Licensing Office (ILO) aims to improve services by means of fast, easy, cheap, transparent and accountable. However, complains persist from the permit applicants, the licensing arrangements are still too bureaucratic, time consuming, and costly. The objectives of the study are: (a) To identify policies and regulations related with IUIPHH, (b) To review the substance of IUIPHH and its relevance, and (c) To improve IUIPHH process as regulated by ILO. The method used is descriptive qualitative analysis. The result of the study revealed that there were 14 regulations involved in IUIPHH process and they are inter-section and inter-connection to each other. The policy of ILO establishment in the management of IUIPHH is not effective in its implementation. Because, it still requires a lot of documents to be submitted. For example, to process AMDAL and other technical documents it needs 105 working days for its completion. Meanwhile, Presidential Decree No 97/2014 states that it needs seven working days only. Thus, revising Presidential Decree No. 97/2014 can be considered to improve IUIPHH process. Reducing the imbalance between human resources and limited supporting facilities is another alternative suggested.